Reactive oxygen species production by the spermatozoa of patients with idiopathic infertility: Relationship to seminal plasma antioxidants - (:unkn) unknown (WILLIAMS & WILKINS, 1997)
Purpose: We attempted to determine reactive oxygen species production by the spermatozoa of patients with idiopathic infertility and healthy donors, and observe whether increased production was due to decreased seminal plasma reactive oxygen species scavengers. Materials and Methods: Reactive oxygen species production by spermatozoa and seminal plasma antioxidants was assayed in 18 patients with idiopathic infertility and 10 controls. Reactive oxygen species formation and seminal plasma antioxidants were measured by luminol and lucigenin dependent chemoluminescence, and enzymatic methods, respectively. Results: Higher reactive oxygen species production was observed in 16 of the 18 patients (88.8%, p<0.0001 versus controls). Seminal plasma superoxide dismutase, catalase, glutathione peroxidase and total sulfhydryl group levels in infertile patients were significantly lower than in controls. Conclusions: Decreased seminal plasma antioxidant activity and increased reactive oxygen species production can be responsible for idiopathic male infertility.
Keywords: infertility, male; testis; semen; reactive oxygen species; SPONTANEOUS LIPID-PEROXIDATION; SUPEROXIDE-DISMUTASE; HUMAN SEMEN; CATALASE ACTIVITY; GENERATION; LEUKOCYTES; ANION